2022
DOI: 10.1111/1365-2745.13909
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between water uptake depth and the leaf economic spectrum in a Mediterranean shrubland

Abstract: 1. Water is the most limiting resource for plant survival and growth in arid environments, but the diversity of water-use strategies among coexisting species in dryland communities is not well understood. There is also growing interest in assessing whether a whole-plant coordination exists between traits related to water-use and the leaf economic spectrum (LES).2. We used water stable isotopes (δ 2 H, δ 18 O) to quantify water uptake proportions from different soil depths by 24 species in a Mediterranean shrub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…A comparison of the isotopic composition of plant water with that of its potential sources has served to infer groundwater uptake in arid and semi-arid environments (e.g. Illuminati et al, 2022;Thorburn et al, 1995;Yin et al, 2015), characterize seasonal shifts in root water up-take across the soil profile (Eggemeyer et al, 2009;Schwendenmann et al, 2015), or unveil the use of alternative water sources such as dew or fog (Burgess and Dawson, 2004). In the past decade, methodological advances, such as novel statistical tools (Stock et al, 2018) and high throughput of samples using laser-based instruments (Martín-Gómez et al, 2015), have allowed for significant increases in the spatiotemporal resolution of water isotope data sets that can be used to infer plant water sources.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the isotopic composition of plant water with that of its potential sources has served to infer groundwater uptake in arid and semi-arid environments (e.g. Illuminati et al, 2022;Thorburn et al, 1995;Yin et al, 2015), characterize seasonal shifts in root water up-take across the soil profile (Eggemeyer et al, 2009;Schwendenmann et al, 2015), or unveil the use of alternative water sources such as dew or fog (Burgess and Dawson, 2004). In the past decade, methodological advances, such as novel statistical tools (Stock et al, 2018) and high throughput of samples using laser-based instruments (Martín-Gómez et al, 2015), have allowed for significant increases in the spatiotemporal resolution of water isotope data sets that can be used to infer plant water sources.…”
Section: Introductionmentioning
confidence: 99%
“…We found separation of soil-moisture depletion zones by the different treatment combinations, but our study suggests that factors other than water impact the ability of J. virginiana to co-exist with grasses and other woody species. Furthermore, our data suggest that ecohydrological niche separation among coexisting plant species may not occur in the early life stages of woody species and competition for water may change as the plants adopt different plant water-use strategies [48].…”
Section: Plos Onementioning
confidence: 89%
“…virginiana to co-exist with grasses and other woody species. Furthermore, our data suggest that ecohydrological niche separation among coexisting plant species may not occur in the early life stages of woody species and competition for water may change as the plants adopt different plant water-use strategies [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that climatic water availability and the plant water use strategy exert additional controls on the forest thermal balance, probably through transpiration cooling. The coordination of rooting depth and other plant functional traits linked to water‐use strategies (Illuminati et al., 2022) may underlie the association of the considered traits with the response to increased VPD during hot spells, that included canopy cooling in the driest stands of the most drought‐resistant species (Figure 6h). Finally, we also showed that forest structural characteristics related to surface roughness such as tree height and cover, stand density, and albedo also influence the forest thermal balance, as they affect heat dissipation mechanisms (Muller et al., 2021).…”
Section: Discussionmentioning
confidence: 99%